2020
DOI: 10.3310/hsdr08090
|View full text |Cite
|
Sign up to set email alerts
|

Use of community treatment orders and their outcomes: an observational study

Abstract: Background Community treatment orders are widely used in England. It is unclear whether their use varies between patients, places and services, or if they are associated with better patient outcomes. Objectives To examine variation in the use of community treatment orders and their associations with patient outcomes and health-care costs. Design Secondary ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 57 publications
0
5
0
1
Order By: Relevance
“…13,14 Other studies in England have reported patients on a CTO had more hospital readmissions and spent longer in in-patient care compared with those not on a CTO. 15,16 Despite the sparse evidence on whether CTOs reduce bed use and improve treatment response, they are used extensively in many countries and are often initiated to potentially reduce the risk of self-harm and suicide after discharge.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 Other studies in England have reported patients on a CTO had more hospital readmissions and spent longer in in-patient care compared with those not on a CTO. 15,16 Despite the sparse evidence on whether CTOs reduce bed use and improve treatment response, they are used extensively in many countries and are often initiated to potentially reduce the risk of self-harm and suicide after discharge.…”
Section: Introductionmentioning
confidence: 99%
“…There have been several changes in the English mental healthcare system since that time, including decreases in the number of acute beds available and increased use of community treatment orders. 14,22 The MHMDS has large amounts of missing clinical data regarding diagnoses, and because of the nature of the administrative data we could not include a range of individual variables which might explain people's mental health vulnerability to relapse after they were discharged, for example, social support, employment, housing, individual-level deprivation, and receipt of community care and support for mental health. We also had no information regarding the pharmacological treatments people were receiving.…”
Section: Discussionmentioning
confidence: 99%
“…In the NHS, clinicians allocate care clusters for individuals on their mental health caseload. We categorised people into three groups based on other work using this data-set, 14 namely non-psychosis, psychosis and severe psychosis (see Supplementary Table 1 available at ).…”
Section: Methodsmentioning
confidence: 99%
“…Na Itália, país considerado modelo para o Brasil na Reforma Psiquiátrica, os HCTPs já foram extintos e foram criadas as Residências para Execução das Medidas de Segurança 23 . Seguindo outra possibilidade de tratamento, na Inglaterra e no País de Gales existem as chamadas Ordens de Tratamento Comunitário Supervisionado, que obrigam os pacientes pós-alta a cumprir as condições especificadas por seus médicos, sob a possibilidade de um retorno compulsório ao hospital para nova internação 24 . Em contraposição, os Artigos 12 e 14 da Convenção internacional sobre os direitos das pessoas com deficiência tratam, respectivamente, do "Reconhecimento igual perante a lei" e da "Liberdade e segurança da pessoa" e fornecem subsídios para avançarmos ainda mais nessa discussão 25 .…”
Section: Artigo Articleunclassified